The Tadpole of the Microendemic, Bromeligenous Crossodactylodes itambe (Anura, Leptodactylidae) from the Endangered 'Campo Rupestre' of Southeastern Brazil, with Additional Comments on Natural History - Santos, Marcus Thadeu T. [UNESP]; Pezzuti, Tiago Leite; Barata, Izabela Menezes; Fortes Leite, Felipe Sa; Garcia, Paulo Christiano A. (Soc Brasileira Herpetologia, 2017)
We describe the external larval morphology of the microendemic leptodactylid frog Crossodactylodes itambe from the `campo rupestre' of the Espinhaco Mountain Range in the state of Minas Gerais, Brazil. The species identity of the only previously described Crossodactylodes tadpole cannot be confirmed, making this the first description of a tadpole of known taxonomic identity for the genus. The tadpole of C. itambe differs from the previously described Crossodactylodes tadpole in total length, origin of dorsal fin, development of tail musculature, spiracle position, absence of inner wall of spiracle and shape, and direction of vent tube. Characters such as narrow lateral gaps of marginal papillae and the distinct medial serration on the oral face of the upper jaw are proposed as putative synapomorphies for the genus. Tadpoles of C. itambe occur exclusively in the axils of the rupicolous bromeliad Vriesea medusa. Observation on the natural history, eggs, and larvae are also reported.
Keywords: Bromeliad; Espinhaco Mountain Range; Larvae; Paratelmatobiinae; Phytotelmata